PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP BELANJA MODAL PEMERINTAH DAERAH KABUPATEN/KOTA JAWA TENGAH - Rizki Aprillia Isriani, 11.05.52.0083; ., Maryono (Students Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the influence of local revenue,the general allocation fund, a special allocation fund,and gross regional domestic product of the capital expenditures in 35 districts or municipalities in the province of Central Java. The sample in this study covers the whole district or city in the province of Central Java during the years 2010-2013 a total of 140 data, while the next few samples eliminated due to a problem of autocorrelation and a problem of heterokedastistas, so the sample size to 118. Based on research that has been done, the results found that:local revenue a positive effect on capital expenditure significantly,the general allocation fund a positive effect on capital expenditure significantly,a special allocation a negative affect on capital expenditure significantly,regional gross domestic product a positive effect on capital expenditure no significantly.Keywords: Local Revenues, General Allocation Fund, A Special Allocation Fund, Gross Regional Domestic Product and Capital Expenditures